Primary ovarian leiomyoma: a diagnostic dilemma - Prajapati, Shradha; V., Meerabai; M., Jayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Among all benign primary ovarian smooth muscle tumors, ovarian leiomyoma is uncommon accounting for .5-1% of all tumors. most of these are unilateral small in size and generally occur in premenopausal women. this paper presents a case report of primary ovarian leiomyoma i.e. 29 years old women with complaints of abdominal pain. the right ovarian mass was histologically diagnosed as ovarian leiomyoma. unlike other smooth muscle tumors of uterine origin, there are no definite histological criteria to categorize smooth muscle tumor of ovary.